Environmental Science. Earth as a living planet / Daniel B. Botkin, Edward A. Keller - Botkin, Daniel B. [et.al] (Estados Unidos de América: John Wiley & Sons, Inc, 1942)
Environment as an idea, basic issues in environmental science, thinking critically about the environment; earth as a system, systems and change, the biogeochemical cycle; life and the environment, the human population as an environmental, problem, ecosystems and ecological communities, biological diversity and biogeography, biological productivity and energy flow; the earth's biomes, sustaining ling resources, world food supply, effect of agriculture on the environment, wild living resources, plentiful and endangered; energy, some basics, fossil fuels and the environment, alternative energy and the environment, nuclear energy and the environment; water environment, the atmosphere, climate and global, warming, air pollution, indoor air pollution, ozone depletion; environment and society environment economics, urban environment, waste management, minerals and the environment, environmental impact and planning, integrating values and knowledge.
Content, illustrated, map, glossary
Col. Agro
Keywords: 1. ECOLOGY 2. EARTH LIVING PLANET 3. BIOLOGY-POPULATION 4. AGROFORESTRY